(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Japanese storytelling employs a four-part structure known as Ki-Shō-Ten-Ketsu, which focuses on harmony and subtle narrative shifts. In contrast, Western storytelling follows Freytag’s Pyramid, emphasizing conflict and resolution. A prime example of the Japanese style is My Neighbor Totoro, which highlights everyday moments without dramatic climaxes, whereas the Western approach is exemplified by Harry Potter, where conflict and resolution drive the narrative. Themes in Japanese storytelling often revolve around harmony, teamwork, and acceptance, subtly teaching moral lessons. Stories like The Crane Wife reflect these values. Meanwhile, Western storytelling emphasizes individual success, bravery, and overcoming challenges, as seen in Spider-Man, where personal growth and responsibility are central. Audience expectations also differ significantly. Japanese audiences appreciate open-ended stories that encourage introspection, such as Akira Kurosawa’s Rashomon, which leaves the truth ambiguous. In contrast, Western audiences prefer stories with explicit resolutions and clear moral lessons, exemplified by The Lion King, where themes of responsibility and redemption are straightforward. Blending these distinct storytelling styles has led to innovative narratives. For instance, Avatar: The Last Airbendercombines Japanese themes of harmony with Western conflict-driven resolutions, appealing to diverse audiences while respecting cultural elements. Ultimately, storytelling reflects cultural values and fosters cross-cultural understanding. Recognizing and appreciating diverse narrative traditions enriches the global storytelling landscape, creating opportunities for empathy and collaboration.